Asuhan Keperawatan Pada Ny. T Dengan Pre Dan Post Op Abses Submandibula Di Ruang Anggrek RSUD Banyumas Kabupaten Banyumas - Riska Meilina; Esti Nur Janah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Submandibular Abscess is an accumulation of pus in the neck space resulting from the spread of infection, most commonly originating from dental infection. This condition requires surgical incision and drainage along with comprehensive nursing care to prevent serious complications. This study used a descriptive method in the form of a case study approach through the nursing process, aimed at describing nursing care for patients with Pre and Post Op Submandibular Abscess. Nursing diagnoses that emerged in Ny. T consisted of five diagnoses: Pre-op: Acute Pain related to physiological injuring agent and Anxiety related to situational crisis. Post-op: Acute Pain related to physical injuring agent, Risk of Infection evidenced by invasive procedures, and Knowledge Deficit related to lack of information exposure. Interventions provided included Pain Management, Relaxation Therapy, Infection Prevention, and Health Education. After nursing implementation for four days (February 12-15, 2026), out of the five diagnoses, two were fully resolved: anxiety and knowledge deficit, while three others were partially resolved due to time constraints, requiring continuous follow-up of nursing care.